Biological aspects of human migration and mobility - C. G. N. Mascie-Taylor; M. Krzyżanowska (Annals of Human Biology, 2017)
This paper reviews how migration, both geographical and social, impacts on variation in some human biological traits. Migration and mobility are considered in relation to anthropometric traits and indices, psychometric traits, health, disease and nutrition, temperature regulation and metabolism, mental health and gene flow. It is well known that migration is important in disease transmission but, as this paper demonstrates, migration can have both positive and negative impacts on both donor and recipient populations for a wide range of human traits.